Health Services in Huntington Disease: A Systematic Literature Review. Issue 1 (11th February 2023) - Mendizabal, Adys; Diaz, Jennifer M.; Bustamante, Arturo V.; Bordelon, Yvette
Abstract : Purpose of Review: Clinical trials for Huntington disease (HD) have primarily focused on managing chorea and, more recently, the development of disease-modifying therapies (DMTs). Nonetheless, understanding health services among patients with HD is essential for assessing new therapeutics, development of quality metrics, and overall quality of life of patients and families with HD. Health services assess health care utilization patterns, outcomes, and health care–associated costs, which can help shape the development of therapeutics and aid in policies that affect patients with a specific condition. In this systematic literature review, we analyze data of published studies looking at causes of hospitalization, outcomes, and health care costs in HD. Recent Findings: The search yielded 8 articles published in the English language and comprising data from the United States, Australia, New Zealand, and Israel. The most common cause of hospitalization among patients with HD was dysphagia or dysphagia-related complications (e.g., aspiration pneumonia or malnutrition), followed by psychiatric or behavioral symptoms. Patients with HD had more prolonged hospitalizations than non-HD patients, and it was most prominent among those with advanced disease. Patients with HD were more likely to be discharged to a facility. A small percentage received inpatient palliative care consultation, and behavioral symptoms were a primary cause of discharge to another facility. Interventions such as gastrostomy tube placement had associated morbidity, and it was common among patients with HD with a diagnosis of dementia. Palliative care consultation and specialized nursing care were associated with more routine discharges and fewer hospitalizations. In terms of cost, patients with HD with private and public insurances had the highest expenditure with more advanced disease, and expenses were associated with hospitalization and medication costs. Summary: In addition to DMTs, HD clinical trial development should also consider the leading causes of hospitalization, morbidity, and mortality in patients with HD, including dysphagia and psychiatric disease. No research study, to our knowledge, has systematically reviewed health services research studies in HD. Evidence from health services research is needed to evaluate the efficacy of pharmacologic and supportive therapies. This type of research is also critical in understanding health care costs associated with the disease and to better advocate and shape policies that can benefit this patient population.